Arthroscopic Hip Labral Reconstruction: Treatment of Irreparable Labral Tears With Segmental Allograft Reconstruction - Mario Hevesi MD, PhD; Lakshmanan Sivasundaram MD; Morgan W. Rice BS; Katlynn Paul BS; Shane J. Nho MD, MS (SAGE Publishing, 2022)
Background: At the time of hip arthroscopy, some patients are found to have irreparable labral tears that are not amenable to primary repair. For these patients, treatment with segmental reconstruction is a surgical option to restore labral tissue and biomechanics. Indications: Patients with segmental irreparable hip labral tears that are technically not amenable for primary labral repair should be considered for labral reconstruction with allograft. Technique Description: Standard hip arthroscopic portals are established. An interportal capsulotomy is performed, and acetabular rim trimming is performed to remove the pincer deformity. Visualized segmental labral defects are measured using a piece of suture to allow for measurement of a curved surface and 1.4-mm polyether ether ketone (PEEK) anchors are placed in anticipation of labral fixation. On the back table, the tibialis anterior allograft is prepared for labral reconstruction. We mark a central portion of the graft tissue based on the measured defect size. A 3-0 vicryl suture is used to place a running stitch from one end to the other of the marked portion of the allograft and the marked, prepared graft is sharply divided from the rest of the tissue. Stitches from the anterior and posterior anchors are passed through the graft using a free needle. The graft is then placed through the distal accessory anterolateral portal and positioned into place. The posterolateral and then medial-most anchors are secured and tied using arthroscopic knots, followed by sequential tying of the middle anchors. Any additional arthroscopic procedures, such as cam resection, are performed, and capsular/skin closure is performed using standard methods. Results: Published outcomes support reconstruction of the labrum using allograft, with 2 series consisting of a total of 141 segmental/circumferential reconstructions demonstrating similar outcome scores at 2 years of follow-up as compared to matched cases of primary labral repairs. Discussion/Conclusion: Hip segmental labral reconstruction with tibialis anterior allograft provides a viable surgical option for patients with labral defects precluding primary labral repair. The presented material demonstrates a readily employable technique as well as clear, step-by-step postoperative rehabilitation protocols, and satisfactory published short- and mid-term outcomes literature.